CULTURIZATION OF LEGAL REVIEWS FOR VICTIMS OF ONLINE CHILD SEXUAL EXPLOITATION AND ABUSE - Erma, Zetria (Universitas Negeri Medan, 2024)
Legal protection for children who are victims of online sexual exploitation (online Child Sexual, Exploitation and Abuse or OCSEA) is an important issue in efforts to safeguard children's rights and welfare in the current era of digitalization. In an effort to overcome this problem, it is necessary to carry out community service by providing counseling for victims of child exploitation cases in the Medan Amplas District of Medan. This community service aims to provide understanding to the community about the importance of joint prevention efforts carried out by parents and teachers regarding the positive and negative impacts of the internet on children. The methodology involves a number of activities with a focus on outreach, training and campaigns to increase public awareness in collaboration with commissions and related institutions. The team also provides educational materials for using the internet to avoid negative risks which can be accessed by the public for free. The result of this community service is increased public awareness, namely the importance of parental and teacher supervision in optimizing internet use properly. Providing legal information related to crimes of sexual exploitation of children online. In conclusion, this community service is a proactive step in dealing with the serious problem of sexual exploitation crimes involving children online. By conducting this activity and the collaboration of several parties, it can jointly protect the younger generation from current technological advances.